2011
DOI: 10.1523/jneurosci.1347-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Link between Area MT Neural Fluctuations and Detection of a Brief Motion Stimulus

Abstract: Fluctuations of neural firing rates in visual cortex are known to be correlated with variations in perceptual performance. It is important to know whether these fluctuations are functionally linked to perception in a causal manner or instead reflect non-causal processes that arise after the perceptual decision is made. We recorded from middle temporal (MT) neurons from monkey subjects while they detected the random occurrence of a brief 50 ms motion pulse that occurred in either of two (or simultaneously in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…Attention [56] can modulate the activity of select neurons as well as affect the subject's behavior; thus it is a good candidate for the source of top-down behavioral sensitivity. Trial-to-trial fluctuations in attention could equally as well have been the source of behavioral sensitivity in studies that otherwise supported a bottom-up model [15,21,35]. Furthermore, two recent multielectrode studies were able to estimate the level of attention on each trial, from the collective responses of many simultaneously recorded neurons [33,34]; it was found that fluctuations in attention could account for the behavioral sensitivity of V4 neurons.…”
Section: Evidence Of Bottom-up and Top-down Sources Of Behavioral Senmentioning
confidence: 99%
See 4 more Smart Citations
“…Attention [56] can modulate the activity of select neurons as well as affect the subject's behavior; thus it is a good candidate for the source of top-down behavioral sensitivity. Trial-to-trial fluctuations in attention could equally as well have been the source of behavioral sensitivity in studies that otherwise supported a bottom-up model [15,21,35]. Furthermore, two recent multielectrode studies were able to estimate the level of attention on each trial, from the collective responses of many simultaneously recorded neurons [33,34]; it was found that fluctuations in attention could account for the behavioral sensitivity of V4 neurons.…”
Section: Evidence Of Bottom-up and Top-down Sources Of Behavioral Senmentioning
confidence: 99%
“…These neurons were recorded from two experiments, while monkeys performed either a motion detection [35] or a speed detection task [31]. These two experiments were combined because they were both detection tasks that used short, transient stimuli (~50 ms), as illustrated in Figure 3A.…”
Section: Properties Of Behavioral Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations